Biotechnological Significance and Applications of Alkaline Protease: A Review (Journal of Environmental Bioremediation and Toxicology, 2023)
Because they catalyze reactions without changing themselves, enzymes are like catalysts in nature. Any enzyme that hydrolyzes the peptide bonds that connect amino acids in a polypeptide chain is considered a protease and initiates protein catabolism. They are useful for both synthetic and degradative purposes. Enzymes are most often found in microbes, and they are more active and stable than enzymes found in plants or animals. Because they multiply quickly, take up little room, and are amenable to genetic manipulation, microbes are a great choice for producing enzymes because we can easily change their features to suit our needs. Different proteases are known as endopeptidases or exopeptidases, depending on whether they work at or away from the termini. On the other hand, proteases are categorized as acidic, alkaline, or neutral depending on their ideal pH. Here we had a look at the many biotechnological uses of alkaline proteases, including in the food, tannery, brewery, silver recovery, and other industrial sectors as well as in medicine, ecology, and sustainability initiatives. The purification processes as well as the optimum condition of the protease was also discussed, in order to provide a comprehensive review about applications of alkaline proteases for sustainable development.
Keywords: Proteases; alkaline; microbes; biotechnology; review